Poluição difusa decorrente da aplicação de água residuária da suinocultura em solo cultivado com soja sob condições de chuva simulada - Bosco, Tatiane Cristina Dal (2007)
West of Paraná presents as outstanding economical activity the swine activity. The effluent of swine generated in the agricultural properties are known by its high pollutant potential. Usually the effluents are treated and later applied to the soil as manuring form and reuse of water. However, these applications happen without a defined rate that considers the soil conditions, climate and cultures cultivated in the area. As a consequence, it can cause problems related to the diffuse pollution due to the runoff and the ions movement in the profile of the soil. So, the objective of this work was to evaluate the diffuse pollution, in terms of total nitrogen, nitrate, nitrite, phosphorus, copper and zinc, due to the application of swine wastewater (ARS) in soil cultivated with soybean, under simulated rain condition. The experiment was installed in November of 2006, in the experimental farm of PUCPR, campus of Toledo where five rates of ARS were applied to the soil (0, 50, 100, 150 and 200 m3 ha-1 in the cycle), in three repetitions for treatment, divided in six applications along the cycle of the soybean. Gutters to collect the runoff material were installed and it was made six rain simulations during the experiment, resulting in six collections of the runoff material that was analyzed pH, total nitrogen, nitrate, nitrite, phosphorus, copper and zinc. At the end of the cycle of the soybean soil samples were collected of each one of the experimental parcels. It was analyzed pH, total nitrogen, nitrate, phosphorus, cation exchangeable capacity, organic matter, copper and zinc of the soil. It was observed that the phosphorus, the total nitrogen, the copper and the zinc were the elements that represented larger concern in terms of pollutant potential of the superficial waters by the runoff. The largest copper, zinc and nitrite concentrations were observed in the initials collections, while the largest concentrations of nitrate and phosphorus were verified in the final collections. In the soil, the effect of ARS was just verified for the cation exchangeable capacity and nitrate.